Model Kepemimpinan Pendidikan Imam Al-Ghazali dan Ibnu Qayyim Al-Jauziyyah - Supian, Sopwan; Bachtiar, Machdum; Muslihah, Eneng (Universitas Pahlawan Tuanku Tambusai, 2024)
The educational leadership model of Imam al-Ghazali and Ibnu Qayyim Al-Jauziyyah is a leadership approach based on the teachings and thoughts of famous Islamic philosophers. Imam Al-Ghazali was an 11th century Islamic scholar known for his contributions to the fields of philosophy, theology, and education. This educational leadership model combines the principles of Islamic education and the leadership concept developed by Imam Al-Ghazali. In this model, educational leadership is seen as having a very important role in guiding students and teachers and motivating them to achieve educational goals. Imam Al-Ghazali emphasized the importance of fair, wise and moral leadership in the field of education. This model explains several main principles underlying Imam Al-Ghazali's educational leadership. Imam Al-Ghazali's educational leadership model is based on Islamic morals: leadership based on Islamic values, deep understanding of students, character development, exemplary leadership, teamwork and consultation, as well as continuous educational improvement and prioritizing a holistic educational approach , including aspects of ethical education. This creates an educational environment that supports the development of students' character and personality and helps them become better humans in society. By following these principles, educational leaders can bring positive change to the world of Islamic education. Then, Ibn Qayyim al-Jawziyyah had noble morals, a calm demeanor in social interactions, a high spirit and broad insight, and was superior in character, goodness, knowledge, virtue, tahajjud, and worship that included the people. Ibnu Qaim al-Jauziyyah studied various sciences such as fiqh from Sheikh Shafiyuddin Al-Hindi, Sheikh Ibnu Taimiyyah, and Sheikh Ismail bin Muhammad Al-Harani. He wrote Al-Rawdaa by Ibn Qudma Al-Maqdisi, Al-Iqam by Al-Amidi, Al-Muhasar by Al-Razi, al-Mawshur, Arbain, and At-Taimiyah.